3D Processing Maps of Cast Mg-9Gd-3Y Alloy and Numerical-Experimental Verification. (12th July 2021) - Li, Pan; Luo, Jianguo
Abstract : The hot compression behavior of Mg-9Gd-3Y (GW93) alloy was investigated by carrying out isothermal compression tests at the deformation temperature range of 300–450°C and strain rate range of 0.001–1s −1 . Considering the influence of the strain on the formability of the GW93 alloy, three-dimensional (3D) processing maps were established based on the dynamic material model. The 3D processing maps indicate that the formability of the material improved with the decrease of the strain rate and the increase of the heating temperature, and the material at lower heating temperature mostly underwent flow instability. The formable processing region of the hot deformation of the GW93 alloy was concentrated within the temperature range of 380–450°C and the strain rate range of 0.001–0.01 s −1 . Subsequently, the 3D processing maps were embedded into the finite element (FE) software DEFORM-3D by means of user subroutines, and the formability of GW93 alloy during the isothermal plane strain forging process was predicted. The FE simulation results revealed that the formability of the material at low strain rate improved compared with that at high strain rate under the same temperature. Finally, an isothermal plane strain forging technological experiment was carried out, and the microstructure of the formed sample was analyzed. The experimental result is in good agreement with that of the numerical simulation. Combined with microstructural observation, the accuracy of the simulation results and the 3D processing maps of the GW93 alloy was verified.